Reconsidering fetal and neonatal alloimmune thrombocytopenia with a focus on screening and prevention. Issue 5 (October 2010) - Skogen, Bjørn; Killie, Mette Kjær; Kjeldsen-Kragh, Jens; Ahlen, Maria Therese; Tiller, Heidi; Stuge, Tor B; Husebekk, Anne
Uncertainty regarding the pathophysiology of fetal and neonatal alloimmune thrombocytopenia (FNAIT) has hampered the decision regarding how to identify, follow-up and treat the women and children with this potentially serious condition. Since knowledge of the condition is derived mainly from retrospective studies, understanding of the natural history of this condition remains incomplete. General screening programs for FNAIT have still not been introduced, mainly because of a lack of reliable risk factors and effective treatment. Now, several prospective screening studies involving up to 100, 000 pregnant women have been published and the results have changed the understanding of the pathophysiology of FNAIT and, thereby, the approach toward diagnostics, prevention and treatment in a more appropriate way.